WAKAF UANG DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - Edy Setyawan; Akhmad Shodikin; Burhanuddin Rabbany (IAIN Syekh Nurjati Cirebon, 2019)
The difference perspectives about endowment among fuqaha is closely related to the respective concept of property (mal). The difference is about property in terms of what can be used as endowments. Do the waqf objects do not move, or move. Then can the objects moves such as money be a property that can be endowments. What is the formulation of the problem are What is meant by money waqf according to Sayyid Sabiq and Law No. 41 of 2004? Why is there a difference between the money waqf law of Sayyid Sabiq and Law No. 41 of 2004? What is the relevance of money waqf in Indonesia by using the rupiah currenlcny?This thesis research is library research. The method used is a qualitative method with a normative - juridical approach. The goals to be achieved with qualitative analysis are to explain a situation, or to analyze the validity of money waqf according to Law No. 41 of 2004 and the invalidity of money endowments according to the views of Sayyid Sabiq. In data analysis, the writer uses descriptive analysis method.The results of the discussion show that according to Sayyid Sabiq the waqf of legal money is invalid. According to him, if someone who will represent something that shows the waqf, it must be on condition that there is the possibility of benefiting from the goods being represented, with the item itself still in existence (baqau ‘ainihi). The legal reason for Sayyid Sabiq who argues that the endowment of illegitimate money is because the money endowments cannot be fixed (baqau ‘ainihi) when used to buy things such as candles, food, and perfume. The opinion of Sayyid Sabiq who considers the invalidity of money waqf is not relevant to the waqf regulations that apply in Indonesia. Because based on the legislation that applies waqf is not enough only with immovable objects but also includes moving objects such as money. This can be accessed from the types of endowments in Indonesia based on Law Number 41 of 2004 concerning Waqf and Government Regulation Number 42 of 2006 concerning the implementation of Law Number 41 of 2004 concerning Waqf, even though the currency in Indonesia uses the Rupiah is still dependent on foreign currency so it is feared that in the coming years there will be inflation, therefore every nominal represented by waqf there must be reserves in the form of gold, because gold tends to be stable and even the selling price